Skip the buffet, for SPARC’s sake - Zhai, Lukai; Krawczyk, Connie M. (Immunity (Cambridge, Mass.), 2022)
Caloric restriction (CR) reduces inflammation and the incidence of chronic diseases, thereby extending healthspan and lifespan. In this issue of Immunity, Ryu et al. (2022) propose that reduction of SPARC, a matricellular protein, during CR offers beneficial effects by reducing SPARC-driven inflammatory phenotypes in macrophages.Caloric restriction (CR) reduces inflammation and the incidence of chronic diseases, thereby extending healthspan and lifespan. In this issue of Immunity, Ryu et al. (2022) propose that reduction of SPARC, a matricellular protein, during CR offers beneficial effects by reducing SPARC-driven inflammatory phenotypes in macrophages.